VATIS update : ozone layer protection. Vol. 4, No. 103, Nov-Dec 2010 - UN.ESCAP; Asian and Pacific Centre for Transfer of Technology (APCTT) (UN.ESCAP. Asian and Pacific Centre for Transfer of Technology, 2010)
VATIS Update Ozone Layer Protection is published 6 times a year to keep the readers up to date of most of the relevant and latest technological developments and events in the field of Ozone Layer Protection. The Update is tailored to policy-makers, industries and technology transfer intermediaries. Highlights : Asteroid strike could deplete ozone layer -- New HFO refrigerant blends -- Aqueous dewaxing system -- Spray foam insulation -- Aerosol fire-extinguishing system -- Novel fumigation formulation THE SCIENCE OF OZONE LAYER . 4 -- Asteroid strike into ocean could deplete ozone layer -- Ozone depletion could be damaging whales’ skin -- Antarctic sea ice increase not linked to ozone hole -- Antarctic ozone hole nears its annual maximum ODS PHASE-OUT IN INDIA . 5 -- Status of ODS phase-out in India -- SAIL phasing out carbon tetrachloride -- National CFC Consumption Phase-out Plan (NCCoPP) -- Workshop on India Chiller Energy Efficiency Project IN THE NEWS . 6 -- Joint WCO/UNEP operation nets large haul of ODS -- China approves use of R-290 refrigerant -- Border meeting on monitoring and controlling trade in ODS -- Ozone Officers training conducted -- Indonesia moves closer to phasing out HCFCs -- Bangladesh phases out ozone depleting substances -- A touch of green in vocational training -- Reiterating zero HCFC commitment -- Updated standards for refrigerant safety REFRIGERATION/AIR-CONDITIONING . 10 -- Integrating CO2 and tri-generation for supermarkets -- Unique drop-in solution for R-22 -- New HFO refrigerant blends -- Climate-friendly refrigerator that runs on HCR-188C1 -- Green products and services from Carrier Corporation -- Refrigerator recycling – post-degasification of polyurethane SOLVENTS . 12 -- Environment-friendly powerful degreasing agent -- CFC-free testing of oil and grease in water -- Aqueous dewaxing system -- Aqueous cleaning solutions FOAMS . 14 -- Spray foam insulation -- Hydrofluoropropene blowing agents -- Inflammable blowing agent control and blend systems HALONS . 15 -- Aerosol ...